Molecular Level Characterization of Circulating Aquaporin-4 Antibodies in Neuromyelitis Optica Spectrum Disorder. Issue 5 (September 2021) - Li, Jie; Bazzi, Sam A.; Schmitz, Florian; Tanno, Hidetaka; McDaniel, Jonathan R.; Lee, Chang-Han; Joshi, Chaitanya; Kim, Jin Eyun; Monson, Nancy; Greenberg, Benjamin M.; Hedfalk, Kristina; Melamed, Esther; et al.
Abstract : Objective: To determine whether distinct aquaporin-4 (AQP4)-IgG lineages play a role in neuromyelitis optica spectrum disorder (NMOSD) pathogenesis, we profiled the AQP4-IgG polyclonal serum repertoire and identified, quantified, and functionally characterized distinct AQP4-IgG lineages circulating in 2 patients with NMOSD. Methods: We combined high-throughput sequencing and quantitative immunoproteomics to simultaneously determine the constituents of both the B-cell receptor (BCR) and the serologic (IgG) anti-AQP4 antibody repertoires in the peripheral blood of patients with NMOSD. The monoclonal antibodies identified by this platform were recombinantly expressed and functionally characterized in vitro. Results: Multiple antibody lineages comprise serum AQP4-IgG repertoires. Their distribution, however, can be strikingly different in polarization (polyclonal vs pauciclonal). Among the 4 serum AQP4-IgG monoclonal antibodies we identified in 2 patients, 3 induced complement-dependent cytotoxicity in a model mammalian cell line ( p < 0.01). Conclusions: The composition and polarization of AQP4-IgG antibody repertoires may play an important role in NMOSD pathogenesis and clinical presentation. Here, we present a means of coupling both cellular (BCR) and serologic (IgG) antibody repertoire analysis, which has not previously been performed in NMOSD. Our analysis could be applied in the future to clinical management of patients with NMOSD to monitor disease activity over time as well as applied to other autoimmune diseases to facilitate a deeper understanding of disease pathogenesis relative to autoantibody clones.